Unemployment and happiness - Rainer Winkelmann (IZA World of Labor, 2014)
Many studies document a large negative effect of unemployment on happiness. Recent research has looked into factors related to impacts on happiness, such as adaptation, social work norms, social capital, religious beliefs, and psychological resources. Getting unemployed people back to work can do more for their happiness than compensating them for doing nothing. But not all unemployed people are equally unhappy. Understanding the differences holds the key to designing effective policies, for helping the unemployed back into work, and for more evenly distributing the burden of unemployment resulting from economic restructuring.
Keywords: I31; I38; J01; J65; 330; unemployment; happiness; social capital; social norms; psychological scarcity